2020
DOI: 10.1111/echo.14664
|View full text |Cite
|
Sign up to set email alerts
|

Our Italian experience using lung ultrasound for identification, grading and serial follow‐up of severity of lung involvement for management of patients with COVID‐19

Abstract: Lung ultrasound (LU)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
182
1
16

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 185 publications
(208 citation statements)
references
References 12 publications
(8 reference statements)
9
182
1
16
Order By: Relevance
“… 16 Sonographically, ground-glass opacities are seen as coalescing B-lines, which were identified in 2 of our patients. 6 , 7 Notably, B-lines are a nonspecific reverberation artifact that may be caused by multiple lung pathologies including pneumonia, pneumonitis, atelectasis, pulmonary contusion or infarction, pleural disease, and neoplasia. 17 …”
Section: Review Of the Literaturementioning
confidence: 99%
“… 16 Sonographically, ground-glass opacities are seen as coalescing B-lines, which were identified in 2 of our patients. 6 , 7 Notably, B-lines are a nonspecific reverberation artifact that may be caused by multiple lung pathologies including pneumonia, pneumonitis, atelectasis, pulmonary contusion or infarction, pleural disease, and neoplasia. 17 …”
Section: Review Of the Literaturementioning
confidence: 99%
“…It, therefore, seems premature to be able to affirm definitive data regarding the performance of thoracic ultrasound examinations until results are available on a large population of COVID-19-positive patients. 8…”
mentioning
confidence: 99%
“…The lung Point of care Ultrasound (POCUS) is reported to be useful in con rming clinical suspicion of COVID 19 infection in patients who showed negative RT-qPCR. [23] reported that normal lung US shows A (complete or partial) lines that are a repetition of the pleural line at the same distance from skin to the pleural line, indicative of air below the pleural line, corresponding to the parietal pleura, and B lines that arise from the pleural line and move in concert with a sliding lung and described as hyperechoic laser-like artefacts that resemble a "comet tail". In pathological lungs, A lines are generally not present and B lines are associated with an interstitial syndrome and diminished lung aeration.…”
Section: Discussionmentioning
confidence: 99%